Left ventricular perforation after Impella® placement in a patient with cardiogenic shock. Issue 5 (25th September 2017) - Peritz, David C.; Linstroth, Lee; Selzman, Craig H.; Gilbert, Edward M.
Abstract: Mechanical cardiovascular support devices are now widely used both in the setting of cardiogenic shock as well as during high risk cardiac catheterization procedures. We report a case of a young female patient who presented with presumed myocarditis and rapidly deteriorating decompensated heart failure requiring the implantation of an Impella Circulatory Support System. Upon transfer to our facility it was discovered that during transport, the Impella device had migrated through the left ventricle. She was emergently taken to the operating room where the Impella was surgically removed and biventricular support devices were placed. The patient eventually expired after weeks of treatment in the intensive care unit. We believe this is the first recorded case of an Impella device perforating the left ventricle. Particularly in cases of newly discovered pericardial effusion, change in waveform on the Impella controller placement signal or rapid decompensation, physicians should consider this rare but potentially catastrophic complication associated with mechanical left ventricular support devices.